2022
DOI: 10.46717/igj.55.1c.4ms-2022-03-23
|View full text |Cite
|
Sign up to set email alerts
|

Soft Soil Treated with Waste Fluid Catalytic Cracking as a Sustainable Stabilizer Material

Abstract: This research aims to stabilize clayey soil utilizing fluid catalytic cracking with an unchangeable ordinary portland cement ratio of 3 percent. A soft clayey soil was blended with 1.5, 3, 4.5, and 6 percent of fluid catalytic cracking by the dry stabilized soil weight, the ordinary portland cement amount has been fixed at 3 percent. The adding of different FCC ratios impact cement stabilized soil evaluated based on the results of unconfined-compressive-strengths test that gained after curing for 7 and 28 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Ordinary Portland cement (OPC) is a type of cement that is commonly utilized in concrete and mortar. It is made by heating limestone and clay at high temperatures and grinding the resulting material into a fine powder [1][2][3]. OPC is the most common type of cement utilized in various applications, including foundations, driveways, sidewalks, and walls.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ordinary Portland cement (OPC) is a type of cement that is commonly utilized in concrete and mortar. It is made by heating limestone and clay at high temperatures and grinding the resulting material into a fine powder [1][2][3]. OPC is the most common type of cement utilized in various applications, including foundations, driveways, sidewalks, and walls.…”
Section: Introductionmentioning
confidence: 99%
“…Portland cement is an essential concrete component, producing significant amounts of CO2 throughout its manufacturing process [7]. The primary sources of CO2 emissions come from burning fossil fuels (coal and natural gas) utilized to heat the rotary kiln and from the calcination process [8,9]. Other sources of emissions include the burning of fuels to drive the grinding and mixing equipment and the movement of materials throughout the cement manufacturing process [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality performance, long-term quantity, rates of surface infiltration, the kinds of permeable pavement, infiltration over low-permeability soils, clogging, and the consequences of urban heat islands have all been examined by researchers [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…analyzed African vegetation dynamics utilizing the NDVI considered by using pictures at a determination to 8 km 2 for now being created for entire of Africa to show NDVI. It has been found that there is vegetation checking using NDVI pictures ought to be related to scene stratification agreeing to cover sort (Al-Masoodi et al, 2021;Townshend and Justice, 1986). Satellite pictures is investigated based on NDVI.…”
Section: Introductionmentioning
confidence: 99%